Digital watermarking for mammogram authentication - Abdul Manaf, Azizah; Zeki, Akram M.; M. Foozy, Feresa (2010)
The advances in multimedia and communication technology nowadays have provided new ways to store, access and distribute medical data in a digital format. Hence, by identifying best location on the mammogram to embed the patient's information without affecting the quality of the image will be studied. The development of authentication techniques for mammogram watermarking can be as one of the alternatives to overcome the weaknesses of losing and mishandling of medical images that will risk the patients. By embedding watermarking in medical image will be easier to identify the medical image by authenticating the patient identity. The paper aim for this research is to identify the best location on the mammogram to embed the patient's information without affecting the quality of the image and to develop an authentication technique of watermarking mammogram using the least significant bits LSB technique.